Interpret the darkness: caves, rock art and analysis of simulated light through virtual scenes - Camilo Barcia García; Alfredo M. Maximiano Castillejo (Virtual Archaeology Review)
Advances in digital technology have raised the capacity of capturing, processing and analyzing spatial data, bringing realistic and accurate reproductions of the elements in archaeological spaces. Current hardware and software have great potential in modelling phenomena and simulating their parameters, leading effective resources to these archaeological issues that have been hard to tackle until recent dates (intrusive techniques, heritage risk, hidden places, unavoidable impediments…). Thus, to approach contextual implications, we propose lighting simulation in aphotic sites as a procedure to study spatial relations between social agents and elements. In this paper we relate the necessary light intensity, its spatial distribution, and any derived implications for activity performing, especially in rock art production and visualization.